Disability, Mental Illness, and eLearning: Invisible Behind the Screen - Kent, Michael (CUNY Graduate Center, 2015)
This article reports on a recent study of students who registered for disability support while studying fully online through Open Universities Australia. The first stage of research was a survey of students who registered for disability support with the organization. This survey found a very high proportion of these students–44.9 percent–identified as people with a mental illness, prompting a second stage of the research where students who had identified as a person with mental illness were interviewed individually. Using this data, the article explores some of the benefits and potential problems students with disabilities experience while studying online, before focusing more specifically on the implications for people with a mental illness. The paper then looks at how mental disability remains a relatively unexplored area of inquiry and how this can partly be explained through the contested place that mental illness holds as an impairment in the broader field of disability studies, particularly in relation to the social model of disability. Finally the article concludes by making a call for further research into best practice for online technological and pedagogical design to better support and enable this group of students. It recommends how the potentially disabling structures of academic institutions could be reformed to better enable a more accessible learning environment. The first step in this process is to recognize these students as having a legitimate impairment that needs to be addressed and accommodated in the contemporary higher education environment.